O corpo gordo: uma cartografia do imaginário social - Nechar, Patrícia Assuf (2020)
In the context of contemporary culture and communicational processes that circulate in thenetworks, the issue of the fat body is debated from different perspectives. In the present doctoral thesis, the fat body is understood as a complex phenomenon, which includes physical, subjective and cultural dimensions. Thus, considering its multiple layers, we seek to contribute to the discussions about the fat body from the development of a social imaginary cartography. Our cartography is based on the study of reports of experiences and memories of women who have had the experience of the fat body in a society where the thin body is the ideal health and beauty. The thesis is in accordance with the epistemological proposal of the program’s Processes of Creation and Communication in Culture line of research. The adopted research method is the cartography of the imaginary that emerges from life stories. The theoretical basis is interdisciplinary in nature and includes: Jung, Campbell and Whitmont, for their studies on myths and female archetypes; Monteiro and Paiva, for the conceptualization of the feminine; Nechar, Aires and Jimenez, for their researches on fat body favorable social movements; Durand's theory of the imaginary; and Leão for the life story and social imaginary cartography. Analyzes were carried out based on the following criteria: memories of family culture; adolescence; Self-perception; body positivity and body neutrality; plus size movement. The research results indicate that there are patterns and dominant structures in the narratives of life stories and, at the same time, the singularities of each of the women studied. The research results point out to possible dominant patterns and structures in life story narratives and, at the same time, the singularities of each of the women studied